Compassion Practices, Nurse Well-Being, and Ambulatory Patient Experience Ratings. Issue 1 (January 2018) - McClelland, Laura E.; Gabriel, Allison S.; DePuccio, Matthew J.
Abstract : Background: Compassion practices both recognize and reward compassion in the workplace as well as provide compassionate support to health care employees. However, these practices represent an underexplored organizational tool that may aid clinician well-being and positively impact patient ambulatory care experiences. Objective: To examine the relationship between compassion practices and nursing staff well-being and clinic-level patients' experience ratings in the ambulatory clinic setting. Research Design: Surveys were collected from ambulatory nurses in January and February of 2015 in 30 ambulatory clinics affiliated with an academic medical center. Patient experience ratings were collected April to June of 2015. Subjects: One hundred seventy-seven ambulatory nurses (Registered Nurses, LPNs, medical assistants), as well as 3525 adult patients from the ambulatory clinics. Measures: Ambulatory nurses assessed compassion practices, emotional exhaustion, and psychological vitality. Patient experience ratings were patient perceptions of courtesy and caring shown by nurses and patients' ratings of the outpatient services. Results: Compassion practices are significantly and negatively associated with nurse emotional exhaustion and positively associated with nurse psychological vitality. At the clinic-level, compassion practices are significantly and positively associated with patient perceptions of caring shown by nurses and overall patient ratings of the outpatient clinic. Supplemental analyses provide preliminary evidence that nurse well-being mediates the relationship between compassion practices and patient ratings of their care experience. Conclusions: Our findings illustrate that compassion practices are positively associated with nurse well-being and patient perceptions of the care experience in outpatient clinics.